Survey of Color Image Compression using Block Partition and DWT Technique - Kulthe, Manjusha Gulabrao; Jaiswal, Priyanka; Chourasia, Bharti (International Journal of Computer Sciences and Engineering, 2019)
In the present era of multimedia, the requirement of image/video storage and transmission for video conferencing, image and video retrieval, video playback, etc. are increasing exponentially. As a result, the need for better compression technology is always in demand. Modern applications, in addition to high compression ratio, also demand for efficient encoding and decoding processes, so that computational constraint of many real-time applications is satisfied. Two widely used spatial domain compression techniques are discrete wavelet transform and multi-level block truncation coding (BTC). DWT method is used to stationary and non-stationary images and applied to all average pixel value of image. Muli-level BTC is a type of lossy image compression technique for greyscale images. It divides the original images into blocks and then uses a quantizer to reduce the number of grey levels in each block whilst maintaining the same mean and standard deviation. In this paper is studied of Multi-level BTC and DWT technique for for gray and color image.